2020
DOI: 10.1007/978-3-030-66504-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Keeping it Human: A Focus Group Study of Public Attitudes Towards AI in Banking

Abstract: While there is substantial interest in ethical practice relating to Artificial Intelligence (AI), to date there has been limited consideration of what this means in the banking sector. This study aimed to address this gap in the literature through a qualitative study of public attitudes and perceptions of current and potential future uses of AI in banking. A series of focus groups were conducted with with diverse members of the public. Focus group participants were largely positive about the role of AI in spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Aside from risks posed to the individual, participants also suggested risks that might harm society and the nation, even though they did not necessarily consider themselves to be personally affected. This is in line with the study on attitudes toward AI in banking conducted by Aitken et al (2020), which found that participants often contemplated AI usage beyond the individual. Table 1 outlines the most frequently discussed types of risk at each level.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Aside from risks posed to the individual, participants also suggested risks that might harm society and the nation, even though they did not necessarily consider themselves to be personally affected. This is in line with the study on attitudes toward AI in banking conducted by Aitken et al (2020), which found that participants often contemplated AI usage beyond the individual. Table 1 outlines the most frequently discussed types of risk at each level.…”
Section: Resultssupporting
confidence: 89%
“…However, few studies adopt a qualitative perspective, although there are some notable exceptions (cf. Aitken et al, 2020; McCradden et al, 2020). Furthermore, the scope of these studies is often confined to what is profitable for companies or governments.…”
mentioning
confidence: 99%